2004
DOI: 10.1111/j.0736-8046.2004.21511.x
|View full text |Cite
|
Sign up to set email alerts
|

The Harlequin Color Change and Association with Prostaglandin E1

Abstract: The harlequin color change is an unusual cutaneous phenomenon observed in newborn infants as transient, benign episodes of a sharply demarcated erythema on half of the infant, with simultaneous contralateral blanching. In this report, two newborns with congenital heart anomalies demonstrated the harlequin color change, one whose skin findings showed a course related to the dose of systemic prostaglandin E1, suggesting a possible association. The benign, self-limited nature of the color change mandates that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 10 publications
(22 reference statements)
1
41
1
Order By: Relevance
“…Apparently, in monozygotic twins, harlequin color change has happened more often in the one with congenital heart disease, and further has disappeared after the heart disease has been cured. 1,[3][4][5]8 To some extent, harlequin color change can be affected by position, and it is easily observed when the subject is lying down on the side. [1][2][3] In our two cases, the presence of RDS, PDA or sepsis may have led to unstable peripheral vasoconstriction causing harlequin color change.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, in monozygotic twins, harlequin color change has happened more often in the one with congenital heart disease, and further has disappeared after the heart disease has been cured. 1,[3][4][5]8 To some extent, harlequin color change can be affected by position, and it is easily observed when the subject is lying down on the side. [1][2][3] In our two cases, the presence of RDS, PDA or sepsis may have led to unstable peripheral vasoconstriction causing harlequin color change.…”
Section: Discussionmentioning
confidence: 99%
“…Usually occurring between two and five days of age, harlequin colour change has been seen as late as three weeks of age. 2 The condition is benign, and the change of colour fades away in 30 seconds to 20 minutes. It may recur when the infant is placed on her or his side.…”
mentioning
confidence: 99%
“…However, it is also stated that this case may have occurred as associated with hypoxia that is another possible launcher of it and may have been linked inadvertently to prostaglandin E1 application. 7 It is thought that the cause of it is vasodilatation due to lack of vascular tone depending on immature hypothalamic or sympathetic system. 5,8 It is also reported that this case may develop depending on traumas preponderant to sympathetic chain, tumours and vascular pathologies.…”
Section: Discussionmentioning
confidence: 99%